A Phantasmatic Reading of Toni Morrison’s Beloved (Damascus University Journal of arts and humanities sciences, 2026)
This research paper discusses the structure of Toni Morrison’s Beloved in terms of the model of the ‘phantasm’ based on Jean Laplanche and J.-B. Pontalis’s essay “Fantasme Originaire, fantasmes des origines, origine du fantasme” (translated into English in 1968 as “Fantasy and the origins of sexuality”). The study focuses on the novel’s shifts from the present to the past which work on revising the past experiences through the light of later events, rather than enforcing the reading of the past influences on the present. Examining the traumatic experiences of Sethe, the novel’s main character, this study argues, exposes the traumatic history which the novel tries to construct in a phantasmatic structure. Starting from her legendary escape and the epic birth of Denver to the killing of her ‘already-crawling?’ baby, Sethe was seen by the ex-slave community as possessing the power of life (giving birth) as well as the power of death (killing her child). Repeated scenarios and incidents in the novel, though with some differences, constitute one form of healing as suggested by Deleuze. The healing of Sethe does not only mean a retranslation of her excessive love for her children, but also a deconstruction and retranslation of life for the black community after slavery.
Keywords: Tony Morrison; Beloved; Phantasm; Psychoanalysis; Jean Laplanche and J.-B. Pontalis; Gilles Deleuze